2014
DOI: 10.1136/jnnp-2013-306389
|View full text |Cite
|
Sign up to set email alerts
|

Delirium and dementia with Lewy bodies: distinct diagnoses or part of the same spectrum?

Abstract: Dementia with Lewy bodies (DLB) is recognised as the second most common form of dementia in older people. Delirium is a condition of acute brain dysfunction for which a pre-existing diagnosis of dementia is a risk factor. Conversely delirium is associated with an increased risk of developing dementia. The reasons for this bidirectional relationship are not well understood. Our aim was to review possible similarities in the clinical presentation and pathophysiology between delirium and DLB, and explore possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 91 publications
(111 reference statements)
0
33
0
9
Order By: Relevance
“…Lewy body disease is the second most common form of dementia in older people with a prevalence of 15%–20% of all dementias at autopsy. 49 The prevalence of older adults with 2 or more DLB symptoms in nursing homes ranges from 16% to 20%. 50 Furthermore, patients with DLB also appear to be more acutely sensitive to minor insults (even subclinical events) and, thus, more delirium “prone.” Consequently, and unsurprisingly, delirium is more commonly diagnosed in DLB than AD 51 with 32% of outpatients with DLB experiencing delirium as opposed to 15% of outpatients with AD.…”
Section: Dementia With Lewy Bodies and The Influence On Tests Used Tomentioning
confidence: 99%
See 1 more Smart Citation
“…Lewy body disease is the second most common form of dementia in older people with a prevalence of 15%–20% of all dementias at autopsy. 49 The prevalence of older adults with 2 or more DLB symptoms in nursing homes ranges from 16% to 20%. 50 Furthermore, patients with DLB also appear to be more acutely sensitive to minor insults (even subclinical events) and, thus, more delirium “prone.” Consequently, and unsurprisingly, delirium is more commonly diagnosed in DLB than AD 51 with 32% of outpatients with DLB experiencing delirium as opposed to 15% of outpatients with AD.…”
Section: Dementia With Lewy Bodies and The Influence On Tests Used Tomentioning
confidence: 99%
“…49 Currently, when there is a suspicion of DLB, diagnostic biomarkers, such as a DaT SCAN may be helpful, 56 although from a practical point of view, these usually need to be performed after the delirium episode ends. The role of objective biomarkers measurements, such as electroencephalography (EEG) to distinguish delirium and DLB, is appealing, however, EEG patterns in delirium overlap with those seen in DLB, making the differentiation more difficult.…”
Section: Dementia With Lewy Bodies and The Influence On Tests Used Tomentioning
confidence: 99%
“…Similar to delirium, Lewy Body Dementia is characterized by fluctuating effects on mental functions, particularly in alertness and attention. 61 Sundown syndrome is another distinct clinical entity formally recognized in the DSM-V that can be difficult to distinguish from delirium. It occurs more frequently in the cognitively impaired or institutionalized patient population but is characterized by behavioral disturbances and mood alteration that occurs specifically in the later afternoon or evening.…”
Section: Gap 4: Patients With Cancer Are Not Routinely Screened Fomentioning
confidence: 99%
“…α-synuclein (α-syn) is a neuronal protein of 140 residues that localizes predominantly to presynaptic terminals (Burre, 2015). There are several similarities in the core features of POD and α-syn-related cognitive disorders, including Parkinson's disease (PD) dementia and dementia with Lewy bodies; these include fluctuating attention, visual hallucinations, and disorganized thoughts (Sunwoo et al, 2013;Gore et al, 2015;Vardy et al, 2015). A previous clinical study demonstrated that αsyn pathologies in the stomach are associated with POD after gastrectomy (Sunwoo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the same research group reported a significant correlation between POD and PD-related non-motor symptoms (Kim et al, 2018). Given that non-motor symptoms may represent the burden of αsyn deposit, POD is thus hypothesized to be a series of αsyn-related cognitive disorders, and maybe a preclinical stage of α-synucleinopathy (Sunwoo et al, 2013;Gore et al, 2015;Kim et al, 2018).…”
Section: Introductionmentioning
confidence: 99%